2021
DOI: 10.1111/bjd.19171
|View full text |Cite
|
Sign up to set email alerts
|

Natural history of naevi: a two‐wave study

Abstract: Summary Background Naevi number changes with age. Thus, a better understanding of naevus biology will shed more light on the genetic and environmental factors involved in melanoma development. Objectives To use a two‐wave study to better understand the evolution of naevi in healthy adults. Methods This study is a prospective two‐wave study based on adult twins from the TwinsUK registry (n = 414) who underwent total body naevus counts with an interval of at least 15 years. A negative binomial hierarchical model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
12
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 30 publications
(60 reference statements)
1
12
0
2
Order By: Relevance
“…In this issue of the BJD , Ribero et al 6 . explore this phenomenon using a longitudinal study design, in which 414 female adult twins in the UK had total‐body naevus counts at least 2 mm in diameter measured 15 years apart (mean age 46 and 63 years, respectively).…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…In this issue of the BJD , Ribero et al 6 . explore this phenomenon using a longitudinal study design, in which 414 female adult twins in the UK had total‐body naevus counts at least 2 mm in diameter measured 15 years apart (mean age 46 and 63 years, respectively).…”
mentioning
confidence: 99%
“…Surprisingly, a systematic review 8 identified only two previous longitudinal studies of adults in the general population, both of which were very small and reported limited data. Thus, the paper by Ribero et al 6 addresses a major gap in our knowledge of the natural history of common melanocytic naevi. Based on their findings, it appears that results from previous cross-sectional studies may reflect a cohort effect rather than a true age effect.…”
mentioning
confidence: 99%
See 3 more Smart Citations